A Judicial Review of the De Facto Detention of Foreigners in Turkey - Ovacik, Gamze (Border Crossing, 2020)
The term, de facto detention, refers to instances in which foreigners are held or deprived of their liberty usually with a view to preventing their entry into a country or expelling them from a country, but without implementing a legally prescribed detention regime that satisfies the criteria of the rule of law. The first type of de facto detention occurs when provisions regulating detention are absent or deficient in the legal framework. The second type takes place when domestic law sufficiently regulates detention regimes; however, the law is not duly implemented in practice. This article examines judicial practices in Turkey in both categories of de facto detention, analysing 37 Turkish court decisions with supporting case law from the European Court of Human Rights. Focusing on case law makes it possible both to track deficiencies in administrative practices and to analyse judicial response as a tool for rectifying unlawful administrative practices.